Identification and Analysis of Dyslipidemia Risk Factors in a Population-Based Study: Data from the Fasa Persian Cohort - Abolfazl Karimivaselabadi; Shahnaz Karimi; Mostafa Bijani; Abdolmajid Ghasemian; Mohammad-Rafi Bazrafshan; Silvia Barbaresi; Mehdi Sharafi; Azizallah Dehghan (Fasa University of Medical Sciences, 2024)
Background & Objectives: Dyslipidemia is a major public health issue worldwide characterized by changes in lipid index such as cholesterol, Low Density Lipoprotein (LDL), High Density Lipoprotein (HDL) and triglycerides (TG).This manuscript aimed to investigate the associated factors of dyslipidemia in Fasa Persian cohort study. Materials & Methods: This cross-sectional study was conducted on the baseline data of Fasa Persian cohort with an initial sample size of 10129 subjects (35-70 years old) in 2021 in Iran. Univariate and multivariate logistic regression models were used to assess the relationship between covariates and dyslipidemia. Results: The number of males in this study was 4572 and the number of females was 5557. The prevalence of dyslipidemia in them was 40.8% and 27.7%, respectively (p-value < 0.001), and the prevalence of dyslipidemia in the whole study population was 3407 (33.6%).  Dyslipidemia was also more common in alcoholics, opium users, smokers, high glycemic index and higher body mass index (BMI). Men were 1.68 times more likely to have dyslipidemia than women. Opium and cigarette smokers were 1.15 and 1.36 times more likely to have dyslipidemia than non-smokers, respectively. Also, as BMI increases, the likelihood of dyslipidemia becomes higher than the reference group (below 18.5), and people with a BMI greater than 30 have the highest obesity range. Conclusions: This study showed that the prevalence of dyslipidemia in the studied population was higher in men than in women and several risk factors such as gender differences, body mass index, smoking and opium use are effective in the prevalence of dyslipidemia.